Оцінка порівняльних переваг Запорізької області у зовнішній торгівлі агропродовольчою продукцією - Почерніна, Наталя Вікторівна; Почернина, Наталья Викторовна; Pochernina, Natalia (My University, 2017)
UK: У статті дана оцінка зовнішньоторговельних переваг регіону у реалізації агропродовольчої продукції. Розраховано коефіцієнт виявленої порівняльної переваги для Запорізької області за період 2010-2015 рр. Здійснено аналіз компаративних переваг регіону у зовнішній торгівлі сільськогосподарською та продовольчою продукцією. Визначено напрями вдосконалення товарної структури регіональної зовнішньої торгівлі агропродовольчою продукцією з метою підвищення вигоди регіону від участі у міжнародному товарному обміні. EN: Efficiency of foreign trade activities is provided with presence and implementation of competitive advantage in international markets. Much of export-import operations in Ukraine accounted for the agricultural sector. Therefore the question of the definition of comparative advantage in exports of agricultural and food products is important as the country level and the level of its separate regions. The main goal of this study is to assess the benefits of Zaporіzhia regions’ comparative advantages in foreign trade of agri-food products. Method of study is calculating the coefficient of the revealed comparative advantage based on a logarithmic function.
Аssessment of Zaporizhia regions’ comparative advantage in foreign trade of agri-food products
Keywords: міжнародна торгівля; порівняльні переваги; коефіцієнт виявленої відносної переваги; агропродовольча продукція; регіон; товарна структура експорту; international trade; comparative advantage; the coefficient of revealed comparative advantage; agri-food product; region; commodity structure of export